2002
DOI: 10.1109/22.981285
|View full text |Cite
|
Sign up to set email alerts
|

Differentially driven symmetric microstrip inductors

Abstract: Abstract-A differentially excited symmetric inductor that enhances inductor quality ( ) factor on silicon RF ICs is presented. Compared with an equivalent single-ended configuration, experimental data demonstrate that the differential inductor offers a 50% greater factor and a broader range of operating frequencies. Predictions from full-wave simulations and a physics-based SPICE-compatible model are validated by experimental measurements on an inductor fabricated in a triple-level metal silicon technology. Ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
101
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(102 citation statements)
references
References 22 publications
1
101
0
Order By: Relevance
“…The parameters are extracted with numerical optimization. In Figs. 11 (a) and (b), self-resonance frequency and Q excited in differential mode improve rather than those excited in single-ended mode due to reduction of parasitic effects in substrate Danesh & Long (2002), which is considerable especially for CMOS LSIs. In common www.intechopen.com Fujumoto et al (2003) as shown in Fig.…”
Section: Measurement and Parameter Extractionmentioning
confidence: 99%
“…The parameters are extracted with numerical optimization. In Figs. 11 (a) and (b), self-resonance frequency and Q excited in differential mode improve rather than those excited in single-ended mode due to reduction of parasitic effects in substrate Danesh & Long (2002), which is considerable especially for CMOS LSIs. In common www.intechopen.com Fujumoto et al (2003) as shown in Fig.…”
Section: Measurement and Parameter Extractionmentioning
confidence: 99%
“…In spite of their widespread use in RFIC design, there is still some misunderstanding about how the differential (common)-mode input impedance Z d (Z c ) must be calculated in terms of S mm when a two-port is seen as a one-port device. Thus, it is usually found that the differential reflection coefficient Γ d of a two-port device is assumed to be S dd [5][6][7][8]. Therefore, the differential input impedance is calculated using the following bilineal impedance transformation…”
Section: Introductionmentioning
confidence: 99%
“…In the past a few decades, great efforts have been devoted to the modeling, optimization and design of the spiral inductors on silicon and GaAs substrates [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. The approaches, such as using high resistive substrate and high conductive metal layers [1], thick dielectric layer [2] or selectively etching off substrates [3], stacking metal layers [4,5], and even differentially driven inductors [6], have been reported. However, to the authors best knowledge, less effort has been found to systematic studies on the performance trends of inductors varying with different geometrical parameters.…”
Section: Introductionmentioning
confidence: 99%